Analysis of Information Technology Governance on Communication and Information Service of Papua Province Using COBIT 2019 - Noelin Huberthina Haay; Melkior N. N Sitokdana (Journal of Information System and Informatics, 2022)
The Communication and Informatics Service of Papua Province is one of the government agencies that has the main task of organizing government affairs in the field of communication and informatics known Diskominfo. The Communication and Informatics Service of Papua Province has implemented IT in its operational processes. In this study using COBIT 2019, determining the domain process to be studied based on the data obtained resulted in capability levels in different MEA Domains. MEA01 is at capability level 4 Customer Focus. MEA02 is at capability level 3 Service/Product Focus. MEA03 is at capability level 5 Business Led. MEA04 is at capability level 4 Customer Focus. IT Governance at the Communication and Informatics Service of Papua Province has been running well but still needs to be developed.